Towards selective phosphodiesterase 2A (PDE2A) inhibitors: a patent review (2010 - present). (2nd August 2016) - Trabanco, Andrés A.; Buijnsters, Peter; Rombouts, Frederik J. R.
ABSTRACT: Introduction : The cyclic nucleotides cAMP and cGMP are ubiquitous intracellular second messengers regulating a large variety of biological processes. The intracellular concentration of these biologically relevant molecules is modulated by the activity of phosphodiesterases (PDEs), a class of enzymes that is grouped in 11 families. The expression of PDEs is tissue- and cell-specific allowing spatiotemporal integration of multiple signaling cascades. PDE2A is a dual substrate enzyme and is expressed in both the periphery and in the central nervous system, however its expression is highest in the brain, where it is mainly localized in the cortex, hippocampus, and striatum. This suggests that this enzyme may regulate intraneuronal cGMP and cAMP levels in brain areas involved in emotion, perception, concentration, learning and memory. Areas covered : This review covers the patent applications published between January 2010 and February 2016 on phosphodiesterase 2A inhibitors. Expert opinion : Recent publications in the literature and in filed patent applications demonstrate the interest of pharmaceutical companies for PDE2A. This has increased the insights of its possible therapeutic role but the few clinical trials were terminated. Based on the ongoing interest in the field it is likely that new clinical trials can be expected and will unravel the therapeutic potential of PDE2A inhibition.